(untitled) (UUM Journal of Legal Studies, 2019)
Right to development covers economic, social, cultural, and political development. Encouraging its subjects to participate actively in economic, social, cultural, and political development, right to development has significant impact on each person. Although it is wide in scope, person, being the central subject of development, this study focuses on right to development of health care professionals limited to doctors and nurses. This paper assessed right to development of health care staff, considering their work conditions and other demographic characteristics. For the implementation of regulations regarding to right to development, a significant fieldwork covering 20 health care institutions in three cities of Turkey was successfully completed. In this fieldwork, Maslach Burnout Inventory (MBI) was used for data collection. This article assessed emotional exhaustion of 185 health workers via SPSS program. The analyse found that education status and type of health care institution have effect on emotional exhaustion while other demographic characteristics such as work experience, annual income or the city were found non-effective on emotional exhaustion of health care professionals. Considering results of this fieldwork, the correlation of emotional exhaustion with the right to development was discussed. The findings reveal that the fear of aggression, lack of sufficient trainings, defamation or mobbing by senior doctors are potential adverse effects causing emotional exhaustion of health workers. To decrease emotional exhaustion caused by work, institutions are suggested to provide ongoing training or a sustainable method for decrement of patient burden and workload. Last but not least, as a sustainable solution, a national wide precise legal monitoring mechanism covering both public and private, ordinary and university health care institutions is strictly offered to be created for prevention of infringement on right to development of medical staff.